Jesus and the Jewish roots of Mary unveiling the Mother of the Messiah - Pitre, Brant James 1975- (New York Image, 2018)
Introduction. The problem with Mary -- The queen of heaven? -- Through ancient Jewish eyes -- The new Eve. The woman in Eden -- Mary the new Eve -- Immaculate Mary -- The new ark. The lost Ark of the Covenant -- Mary the new ark -- Assumed into heaven -- The queen mother. The queen mother in ancient Israel -- Mary the new queen -- Mother of "God with us" -- The perpetual virgin. Mary's Jewish vow -- The brothers of Jesus -- Ever-virgin -- The birth of the Messiah. The mother of the Messiah -- Mary's birth pangs -- Mary's womb and Jesus' tomb -- The new Rachel. Rachel in ancient Judaism -- Mary the new Rachel -- Mother of the church -- At the foot of the cross. Jesus' last words -- He took her to be his own -- Behold, your mother.
"Takes readers step-by-step from the Garden of Eden to the Book of Revelation to reveal where Catholic beliefs about Mary really come from. Dr. Pitre uses the Old Testament and ancient Judaism to show how the Bible itself teaches that Mary is the new Eve, the Mother of God, the Queen of Heaven and Earth, and the new Ark of the Covenant"--
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references
Keywords: Mary -- Blessed Virgin, Saint -- Theology; Mary -- Blessed Virgin, Saint -- History of doctrines; Catholic Church -- Relations -- Judaism; Judaism -- Relations -- Catholic Church